Polarizing film laminate
Patent Information
- Application Number
- CN202180033136.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-08
- Filing Date
- 2021-04-30
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-04-30
AI Technical Summary
In high-temperature environments, the transmittance of polarization film laminates decreases, which is particularly problematic in automotive image display devices where durability is insufficient.
In the polarizing film laminate, a water-soluble free radical scavenger is added between the first substrate and the second substrate, which has a moisture permeability of less than 300 g/(m2·24h), to capture the free radicals generated by the polarizing film in a high-temperature environment and prevent the deterioration of polyvinyl alcohol.
It effectively suppressed the decrease in the single-unit transmittance of the polarizing film under high temperature conditions and improved the durability of the polarizing film laminate.
Smart Images

Figure BDA0003926308600000031 
Figure BDA0003926308600000032 
Figure BDA0003926308600000041
Abstract
Description
Technical Field
[0001] This invention relates to polarizing film laminates. Background Technology
[0002] Previously, polarizing films used in various image display devices such as liquid crystal displays and organic EL displays have employed dyed polyvinyl alcohol (PVA) films (containing dichroic substances such as iodine and dichroic dyes) to achieve both high transmittance and high polarization. These polarizing films are manufactured as follows: after performing various treatments such as swelling, dyeing, crosslinking, and stretching on the PVA film in a bath, the film is cleaned and then dried.
[0003] In recent years, in addition to mobile devices such as mobile phones and tablets, such image display devices have also been used in vehicles such as car navigation systems and rearview monitors, and their applications are expanding. Along with this, compared to previous requirements, polarizing film laminates with polarizing films are now required to have higher durability in harsher environments (such as high-temperature environments), leading to the development of polarizing film laminates designed to ensure such durability (Patent Documents 2-3).
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-102353
[0007] Patent Document 2: Japanese Patent Publication No. 2012-516468
[0008] Patent Document 3: Japanese Patent Application Publication No. 2018-101117 Summary of the Invention
[0009] The problem that the invention aims to solve
[0010] In the aforementioned automotive image display devices, the development of autonomous driving technology in recent years has led to the proliferation of irregularly shaped and larger displays. With these changes in display design, there is a growing demand for methods to further improve the durability of polarizing film laminates in high-temperature environments.
[0011] In view of the above, the object of the present invention is a polarizing film laminate that has excellent effect in suppressing the decrease of monomer transmittance in high temperature environments.
[0012] Problem Solving Methods
[0013] Specifically, this invention relates to a polarizing film laminate, which is a polarizing film laminate in which a first substrate, a polarizing film, and a second substrate are sequentially stacked, wherein the moisture transmittance of the first substrate and the second substrate is 300 g / (m²).2 • 24h or less, at least one layer containing a water-soluble free radical scavenger exists between the first substrate and the second substrate.
[0014] The effects of the invention
[0015] The exact mechanism of action of the polarizing film laminate of the present invention is not fully understood, but it is presumed to be so. However, the present invention is not limited to this mechanism of action.
[0016] The polarizing film laminate of the present invention is a polarizing film laminate in which a first substrate, a polarizing film, and a second substrate are sequentially stacked, wherein the moisture transmittance of the first substrate and the second substrate is 300 g / (m²). 2 (24h or less) At least one layer between the first substrate and the second substrate contains a water-soluble free radical scavenger. It is presumed that the polarizing film undergoes polyolefin formation accompanied by free radical generation due to the degradation of polyvinyl alcohol in a high-temperature environment, resulting in a decrease in monomer transmittance. On the other hand, when the polarizing film laminate of the present invention is exposed to a high-temperature environment, the water-soluble free radical scavenger contained in at least one layer between the first substrate and the second substrate is retained together with the moisture contained in the polarizing film in a region with a transmittance of 300 g / (m²). 2 The first substrate and the second substrate are moved between each other for up to 24 hours, thereby efficiently capturing free radicals generated in the polarizing film and effectively suppressing the decrease in monomer transmittance in high-temperature environments. Detailed Implementation
[0017] The polarizing film laminate of the present invention is a polarizing film laminate in which a first substrate, a polarizing film, and a second substrate are sequentially stacked, wherein the moisture transmittance of the first substrate and the second substrate is 300 g / (m²). 2 • 24h or less, at least one layer containing a water-soluble free radical scavenger exists between the first substrate and the second substrate.
[0018] <Water-soluble free radical scavengers>
[0019] From the viewpoint of easy migration to the moisture in the polarizing film, the aforementioned water-soluble free radical scavenger is preferably capable of dissolving 1 part by weight or more of the compound in 100 parts by weight of water at 25°C, more preferably capable of dissolving 2 parts by weight or more of the compound in 100 parts by weight of water at 25°C, and even more preferably capable of dissolving 5 parts by weight or more of the compound in 100 parts by weight of water at 25°C. The aforementioned water-soluble free radical scavenger can be used alone or in combination of two or more.
[0020] It is presumed that the aforementioned water-soluble free radical scavenger can suppress polyene formation in polarizing films under high-temperature conditions. Examples of such water-soluble free radical scavengers include compounds with free radical scavenging functions such as hindered phenols, hindered amines, phosphorus compounds, sulfur compounds, benzotriazoles, benzophenones, hydroxylamines, salicylates, and triazines. From the viewpoint of the types of free radicals generated in the polarizing film, compounds having nitryl radicals or nitryl groups are preferred as such water-soluble free radical scavengers.
[0021] As for the compounds containing nitryl radicals or nitryl groups mentioned above, from the viewpoint of having relatively stable free radicals at room temperature and in air, N-hydroxyl radical compounds (containing CN(-C)-O) can be cited as examples. · Compounds with functional groups (O) · (This refers to oxygen free radicals), and well-known compounds can also be used. Examples of N-hydroxyl radical compounds include compounds with organic groups having the following structures.
[0022] [Chemical Formula 1]
[0023]
[0024] (In general formula (1), R) 1 R represents oxygen free radicals. 2 ~R 5 The number of hydrogen atoms or alkyl groups with 1 to 10 carbon atoms can be independently represented (n represents 0 or 1). It should be noted that the left side of the dashed part in general formula (1) represents any organic group.
[0025] Examples of compounds having the above-mentioned organic groups include compounds represented by the following general formulas (2) to (5).
[0026] [Chemical Formula 2]
[0027]
[0028] (In general formula (2), R) 1 ~R 5 And n has the same meaning as above, R 6 (This indicates a hydrogen atom, an alkyl group, an acyl group, or an aryl group with 1 to 10 carbon atoms; n represents 0 or 1.)
[0029] [Chemical Formula 3]
[0030]
[0031] (In general formula (3), R) 1 ~R 5 And n has the same meaning as above, R 7 and R 8(Independently representing a hydrogen atom, an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms.)
[0032] [Chemical Formula 4]
[0033]
[0034] (In general formula (4), R) 1 ~R 5 And n has the same meaning as above, R 9 ~R 11 Independently representing a hydrogen atom, an alkyl group, acyl group, amino group, alkoxy group, hydroxyl group, or aryl group having 1 to 10 carbon atoms.
[0035] [Chemical Formula 5]
[0036]
[0037] (In general formula (5), R) 1 ~R 5 And n has the same meaning as above, R 12 (This refers to a hydrogen atom, or an alkyl, amino, alkoxy, hydroxyl, or aryl group having 1 to 10 carbon atoms.)
[0038] In the above general formulas (1) to (5), from the perspective of ease of acquisition, R 2 ~R 5 Preferably, it is an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms. Furthermore, in the above general formula (2), from the viewpoint of ease of acquisition, R... 6 Preferably, it is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, more preferably a hydrogen atom. Furthermore, from the viewpoint of ease of acquisition, R is preferred in the above general formula (3). 7 and R 8 Independently, it is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, more preferably a hydrogen atom. Furthermore, in the above general formula (4), from the viewpoint of ease of acquisition, R... 9 ~R 11 Preferably, it is an alkyl group having 1 to 10 hydrogen atoms. Furthermore, in the above general formula (5), from the viewpoint of ease of acquisition, R... 12 Preferably, it is hydroxyl, amino, or alkoxy. In the above general formulas (1) to (5), from the viewpoint of ease of acquisition, n is preferably 1.
[0039] In addition, examples of the aforementioned N-hydroxyl compounds include those described in Japanese Patent Application Publication No. 2003-64022, Japanese Patent Application Publication No. 11-222462, Japanese Patent Application Publication No. 2002-284737, and International Publication No. 2016 / 047655.
[0040] In addition, the following compounds can be cited as examples of compounds having nitrocellulose radicals or nitrocellulose groups.
[0041] [Chemical Formula 6]
[0042]
[0043] (In general formula (6), R represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group with 1 to 10 carbon atoms.)
[0044] [Chemical Formula 7]
[0045]
[0046] [Chemical Formula 8]
[0047]
[0048] Furthermore, regarding the aforementioned water-soluble free radical scavenger, considering that in a high-temperature environment, the water-soluble free radical scavenger contained in at least one layer between the first substrate and the second substrate, together with the water contained in the polarizing film, can remain (move) between the first substrate and the second substrate, thereby efficiently capturing free radicals generated in the polarizing film, the molecular weight is preferably 1000 or less, more preferably 500 or less, and even more preferably 300 or less.
[0049] <Polarizing film>
[0050] The aforementioned polarizing film is formed by adsorbing dichroic substances such as iodine and dichroic dyes onto a polyvinyl alcohol film and orienting them. From the viewpoint of the initial polarization performance of the polarizing film, an iodine-based polarizing film containing iodine as the aforementioned dichroic substance is preferred.
[0051] The aforementioned polyvinyl alcohol (PVA) films can be used without particular limitation, and are obtained by dispersing and adsorbing dichroic substances such as iodine and dichroic dyes in the visible light region. Examples of materials for the aforementioned PVA films include polyvinyl alcohol or its derivatives. Examples of PVA derivatives include: polyvinyl formal, polyvinyl acetal; olefins such as ethylene and propylene; and derivatives obtained by modifying unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, their alkyl esters, and acrylamide. The average degree of polymerization of the aforementioned PVA is preferably about 100 to 10,000, more preferably about 1,000 to 10,000, and even more preferably about 1,500 to 4,500. Furthermore, the degree of saponification of the aforementioned PVA is preferably about 80 to 100 mol%, more preferably about 95 mol% to 99.95 mol%. It should be noted that the aforementioned average degree of polymerization and degree of saponification can be determined based on JIS K 6726.
[0052] The aforementioned polarizing film is obtained by existing polarizing film manufacturing methods, for example, by performing an optional swelling and cleaning process on the aforementioned polyvinyl alcohol film, and at least performing a dyeing process, a crosslinking process, and a stretching process. When the aforementioned polarizing film contains the aforementioned water-soluble free radical scavenger, the processing bath in any one or more of the aforementioned swelling, cleaning, dyeing, crosslinking, and stretching processes may contain the aforementioned water-soluble free radical scavenger.
[0053] From the viewpoint of improving the initial polarization degree of the polarizing film, the thickness of the polarizing film is preferably 1 μm or more, more preferably 2 μm or more, and from the viewpoint of preventing panel warping, it is preferably 20 μm or less, more preferably 15 μm or less, further preferably 10 μm or less, and even more preferably 8 μm or less. In particular, in order to obtain a polarizing film with a thickness of about 8 μm or less, the following method for manufacturing a thin polarizing film can be applied, in which a laminate comprising a thermoplastic resin substrate and a polyvinyl alcohol resin layer formed on the thermoplastic resin substrate is used as the polyvinyl alcohol film.
[0054] The polarizing film (thin polarizing film) is obtained by existing polarizing film manufacturing methods, for example, by performing the following steps: forming a polyvinyl alcohol resin layer (PVA resin layer) containing polyvinyl alcohol resin (PVA resin) on one side of a strip-shaped thermoplastic resin substrate to prepare a laminate; while transporting the obtained laminate in the length direction, performing any insoluble treatment step, crosslinking treatment step, and cleaning treatment step on the laminate, and performing at least an assisted stretching treatment step in a gas atmosphere, a dyeing treatment step, and a stretching treatment step in an aqueous solution step. When the polarizing film contains the aforementioned water-soluble free radical scavenger, the treatment bath in any one or more of the aforementioned insoluble treatment step, crosslinking treatment step, cleaning treatment step, dyeing treatment step, and stretching treatment step in an aqueous solution step may contain the aforementioned water-soluble free radical scavenger.
[0055] <First substrate and second substrate>
[0056] The first substrate and the second substrate mentioned above only need to have a moisture permeability of 300 g / (m²). 2 For samples with a duration of 24 hours or less, there are no particular restrictions; for example, organic substrates such as transparent protective films and phase retardation films used for polarizing films can be used. The first substrate and the second substrate mentioned above can be the same or different. It should be noted that the moisture permeability can be calculated as follows: According to the moisture permeability test (cup method) of JIS Z0208, a sample cut into 60mm diameter pieces is placed in a moisture permeability cup containing approximately 15g of calcium chloride. The cup is then placed in a constant temperature chamber at 40°C and 90% RH, and the weight increase of calcium chloride before and after 24 hours is measured and calculated.
[0057] Examples of materials constituting the aforementioned transparent protective film include cellulose ester resins, polycarbonate resins, (meth)acrylic resins, cyclic polyolefin resins, and polyester resins. Examples of materials constituting the aforementioned retardation film include birefringent films formed by unidirectional or bidirectional stretching of polymer raw materials, alignment films of liquid crystal polymers, and retardation plates formed by supporting an alignment layer of a liquid crystal polymer with a film. In addition, one or more layers such as hard coatings, anti-reflective layers, anti-adhesion layers, diffusion layers, or anti-glare layers can be provided on the aforementioned transparent protective film and the aforementioned retardation film; optical layers such as reflective plates, semi-transparent plates, retardation plates (including 1 / 2 and 1 / 4 wave plates), and viewing angle compensation films can be used to form image display devices, etc.
[0058] For the first substrate and the second substrate described above, from the viewpoint that the water-soluble free radical scavenger contained in at least one layer between the first substrate and the second substrate, together with the moisture contained in the polarizing film, can remain (move) between the first substrate and the second substrate in a high-temperature environment, thereby efficiently capturing free radicals generated in the polarizing film, the combined moisture permeability of the first substrate and the second substrate is preferably 300 g / (m²). 2 • 24h or less, more preferably 200g / (m 2 • 24h or less, more preferably 100g / (m 2 • 24h or less. Especially when an active energy ray-curable adhesive layer (described later) exists as a layer between the first substrate and the second substrate, the moisture permeability of the first substrate or the second substrate adjacent to this adhesive layer is preferably 100 g / (m²). 2 • 24h or less, more preferably 50g / (m 2 • 24h or less, more preferably 20g / (m 2 ·24h and below.
[0059]
[0060] From the viewpoint that the water-soluble free radical scavenger contained in at least one layer between the first substrate and the second substrate can be retained (moved) together with the moisture contained in the polarizing film in a high-temperature environment, thereby efficiently capturing free radicals generated in the polarizing film, the total thickness of the layer between the first substrate and the second substrate is preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less.
[0061] From the viewpoint that the water-soluble free radical scavenger contained in at least one layer between the first substrate and the second substrate can be retained (moved) together with the water contained in the polarizing film in a high-temperature environment, thereby efficiently capturing free radicals generated in the polarizing film, the total thickness of the layers present between the first substrate and the second substrate is preferably 3 times or less, more preferably 2.5 times or less, and even more preferably 2 times or less, relative to the thickness of the polarizing film.
[0062] In addition to the polarizing film, other layers existing between the first substrate and the second substrate may include adhesive layers, bonding agent layers, and functional layers.
[0063] As the adhesive forming the adhesive layer described above, various adhesives used in polarizing films can be applied, such as acrylic adhesives. Furthermore, as the adhesive forming the adhesive layer described above, various adhesives used in polarizing films can be applied, such as polyvinyl alcohol adhesives and active energy radiation-cured adhesives. As an active energy radiation-cured adhesive, (meth)acrylate adhesives are an example. As the curing component in the aforementioned (meth)acrylate adhesives, compounds having (meth)acryloyl groups and compounds having vinyl groups are examples. As compounds having (meth)acryloyl groups, examples include (meth)acrylate alkyl esters with 1 to 20 carbon atoms, (meth)acrylate alicyclic alkyl esters, (meth)acrylate polycyclic alkyl esters, and other (meth)acrylate alkyl esters; hydroxyl-containing (meth)acrylates; glycidyl (meth)acrylates, and epoxy-containing (meth)acrylates, etc. (Meth)acrylate adhesives may contain nitrogen-containing monomers such as hydroxyethyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, (meth)acrylamide, and (meth)acryloylmorpholine. (Meth)acrylate adhesives may also contain tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecanediethanol diacrylate, cyclic trimethylolpropane methyl acetal acrylate, and di... Multifunctional monomers such as alkyl glycol diacrylate and EO-modified diglycerol tetraacrylate are used as crosslinking components. Additionally, compounds with epoxy groups or oxocyclic butyl groups can also be used as cationic polymerization curing adhesives. There are no particular limitations on compounds with epoxy groups, as long as they have at least two epoxy groups within the molecule; various commonly known curing epoxy compounds can be used.
[0064] Examples of the aforementioned functional layers include a barrier layer that prevents impurities such as oligomers and ions dissolved from the transparent protective film from migrating (invading) into the polarizing film; a refractive index adjustment layer that suppresses the decrease in transmittance caused by reflection between layers with different refractive indices, such as the transparent protective film and the polarizing film; a reinforcing layer that prevents the polarizing film from bending; and a liquid crystal coating with phase difference functionality. It should be noted that, from the viewpoint of efficiently capturing free radicals generated in the polarizing film at high temperatures, the water-soluble free radical scavenger added is preferably added to layers containing PVA-based resins, such as the polarizing film, the water-based adhesive, or the functional layer (reinforcing layer).
[0065] The first substrate, the second substrate, and the layer between the first substrate and the second substrate may be subject to surface modification treatment and easy bonding treatment.
[0066] Example
[0067] The present invention will be described in more detail below with reference to specific embodiments, but the present invention is not limited to these embodiments.
[0068] <Example 1>
[0069] <Production of Polarizing Film>
[0070] A 100 μm thick amorphous polyethylene terephthalate (IPA) copolymer film (PET) substrate with a water absorption rate of 0.75% and a Tg of 75 °C was subjected to corona treatment on one side. On this corona-treated surface, an aqueous solution containing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetyl-modified PVA (degree of polymerization 1200, acetyl-modification rate 4.6%, degree of saponification ≥ 99.0 mol%, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "Gohsefimer Z200") in a 9:1 ratio was coated at 25 °C and dried to form an 11 μm thick PVA resin layer, thus producing a laminate. The resulting laminate was then subjected to longitudinal (length direction) uniaxial stretching (assisted stretching treatment in a gas atmosphere) to 2.0 times its free end length in an oven at 120 °C between rollers with different circumferential speeds. Next, the laminate was immersed in an insoluble bath (an aqueous solution of boric acid prepared by adding 4 parts by weight of boric acid to 100 parts by weight of water) at a liquid temperature of 30°C for 30 seconds (insoluble treatment). Then, it was immersed in a dyeing bath at a liquid temperature of 30°C, adjusting the iodine concentration and immersion time to achieve a given transmittance for the polarizing film (dyeing treatment). Next, it was immersed in a crosslinking bath at a liquid temperature of 30°C (an aqueous solution of boric acid prepared by adding 3 parts by weight of potassium iodide and 3 parts by weight of boric acid to 100 parts by weight of water) for 30 seconds (crosslinking treatment). Then, the laminate was immersed in an aqueous solution of boric acid at a liquid temperature of 70°C (an aqueous solution prepared by adding 4 parts by weight of boric acid and 5 parts by weight of potassium iodide to 100 parts by weight of water) and unidirectionally stretched along the longitudinal direction (length direction) between rollers at different circumferential speeds to achieve a total stretch ratio of 5.5 times (stretching treatment in aqueous solution). Then, the laminate was immersed in a cleaning bath at 30°C (an aqueous solution of 3% potassium iodide and 1% by weight of the compound represented by the following general formula (9) as a water-soluble free radical scavenger) (cleaning treatment). Then, while drying in an oven maintained at 90°C, it was contacted with a heated roller made of SUS at a surface temperature maintained at 75°C for approximately 2 seconds (drying shrinkage treatment). Through the above operations, an optical film laminate containing a polarizing film with a thickness of 5.4 μm was obtained. The content of the free radical scavenger in the polarizing film, determined by the following method, was 0.19% by weight.
[0071] [Chemical Formula 9]
[0072]
[0073] [Method for determining the content (wt%) of water-soluble free radical scavengers in polarizing films]
[0074] Take about 20 mg of polarizing membrane for quantitative analysis. Dissolve it in 1 mL of water by heating, then dilute with 4.5 mL of methanol. Filter the resulting extract through a membrane filter and determine the concentration of water-soluble free radical scavenger in the filtrate using HPLC (Waters ACQUITY UPLC H-class Bio).
[0075] <Fabrication of Polarizing Film Laminates>
[0076] As an adhesive, an aqueous solution containing polyvinyl alcohol resin with acetylacetyl groups (average degree of polymerization 1200, degree of saponification 98.5 mol%, degree of acetylacetylation 5 mol%) and hydroxymethyl melamine in a weight ratio of 3:1 was used. Using a roller laminator, a 30 μm thick transparent protective film (with a moisture permeability of 125 g / (m²)) formed of (meth)acrylic resin (a modified acrylic polymer with a lactone ring structure) was laminated onto the polarizing film surface of the optical film laminate obtained above using the adhesive (dry film thickness 0.1 μm). 2 The first substrate was prepared by heating and drying in an oven (60°C for 4 minutes). Next, the polyethylene terephthalate film was peeled off, and a 27μm thick cyclic olefin resin film (manufactured by ZEON Corporation, Japan, ZF14, moisture permeability 10g / (m²)) was bonded to the peeled side using a UV-curable adhesive. 2 A second substrate was prepared by irradiating the second substrate with UV light for 24 hours to cure the adhesive, thus creating a polarizing film laminate. Details of the UV-curable adhesive are as follows: An adhesive was prepared by mixing 40 parts by weight of N-hydroxyethylacrylamide (HEAA), 60 parts by weight of acryloylmorpholine (ACMO), and 3 parts by weight of the photoinitiator "IRGACURE 819" (manufactured by BASF). The cured adhesive layer was coated onto a polarizing film to achieve a thickness of 1.0 μm, and then cured by irradiating with UV light as the active energy ray. The UV irradiation was performed using a gallium-encapsulated metal halide lamp; the irradiation device was a Light HAMMER10 manufactured by Fusion UV Systems, Inc.; the valve was a V-valve; and the peak illuminance was 1600 mW / cm². 2 Cumulative radiation dose 1000 mJ / cm 2 (Wavelength 380–440 nm) The ultraviolet irradiance was measured using the Sola-Check system manufactured by Solatell.
[0077] <Preparation of Acrylic Adhesives>
[0078] A monomer mixture containing 99 parts of butyl acrylate and 1 part of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet tube, and condenser. Further, relative to 100 parts of the monomer mixture (solid component), 0.1 parts of 2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile) as a polymerization initiator and 100 parts of ethyl acetate were added together. Nitrogen gas was introduced while stirring slowly to purge the mixture. The liquid temperature in the flask was maintained at approximately 55°C, and the polymerization reaction was carried out for 8 hours to prepare a solution of an acrylic polymer with a weight-average molecular weight (Mw) of 1.8 million. Then, relative to 100 parts of the solid component of the obtained acrylic polymer solution, 0.02 parts of isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "Takenate D110N", trimethylolpropane / phenylenedimethyl diisocyanate adduct) and 0.2 parts of silane coupling agent (manufactured by Shin-Etsu Chemical Industry Co., Ltd., trade name "X-41-1056") were added to prepare an acrylic adhesive composition solution.
[0079] <Fabrication of Polarizing Film Laminates with Adhesive>
[0080] The solution of the acrylic adhesive composition obtained above was coated onto one side of a polyethylene terephthalate film (Mitsubishi Chemical Polyester Film, trade name "MRF38", separator) treated with an organosilicon release agent, so that the thickness of the dried adhesive layer was 20 μm. The film was then dried at 90°C for 1 minute, forming an adhesive layer on the surface of the separator. Next, the adhesive layer formed on the separator was transferred to one side of the polarizing film laminate prepared above, thus creating a polarizing film laminate with an adhesive layer.
[0081] [Evaluation of monomer transmittance in high-temperature environments]
[0082] The polarizing film laminate with adhesive layer obtained above was cut into 45×40mm pieces with the absorption axis of the polarizing film parallel to its long side. A glass plate (EG-XG, 50×45mm, 0.7mm thickness, manufactured by Hiraoka Special Glass Co., Ltd.) was then bonded with the adhesive layer. The laminate was then subjected to autoclaving at 50°C and 0.5MPa for 15 minutes to produce the laminate. The resulting laminate was placed in a hot air oven at 105°C for 500 hours, and the single-cell transmittance (ΔTs) before and after heating was measured. The single-cell transmittance was obtained by measuring the optical properties using a UV-Vis spectrophotometer (Otsuka Electronics, "LPF-200"). This single-cell transmittance was obtained by visibility correction using a 2-degree field of view (C light source) according to JlS Z 8701-1982. It should be noted that the measurement wavelength was 380–780nm (in 5nm intervals).
[0083] ΔTs(%)=Ts 500 -Ts0
[0084] Here, Ts0 is the monomer transmittance of the laminate before heating, and Ts 500 The transmittance of the laminate after heating for 500 hours is the monomer transmittance. The results are shown in Table 1. The above ΔTs (%) is preferably 5 ≥ ΔTs (%) ≥ 0, more preferably 3 ≥ ΔTs (%) ≥ 0.
[0085] <Example 2>
[0086] In the fabrication of the polarizing film laminate, a 23 μm thick cycloolefin film (manufactured by ZEON Corporation, Japan, ZF12, with a moisture permeability of 10 g / (m²)) was used. 2 Using 24h)) as the first substrate, and using the UV-curable adhesive described in Example 1 as the adhesive for bonding, a polarizing film laminate with an adhesive layer was fabricated by the same operation as in Example 1.
[0087] <Example 3>
[0088] In the fabrication of the polarizing film, no water-soluble free radical scavenger represented by general formula (9) was added to the cleaning bath. In the fabrication of the polarizing film laminate, a water-soluble free radical scavenger represented by general formula (9) was added to the adhesive used to bond the polarizing film to the first substrate in a weight ratio of 4:3 to polyvinyl alcohol resin. Potassium hydroxide was added in a molar ratio of 1:1 relative to the water-soluble free radical scavenger in a manner that would not affect the curing reaction of the adhesive. The pH was adjusted (for neutralization). Otherwise, a polarizing film laminate with an adhesive layer was fabricated by the same operation as in Example 1.
[0089] <Example 4>
[0090] In the fabrication of the polarizing film, no water-soluble free radical scavenger represented by general formula (9) was added to the cleaning bath. In the fabrication of the polarizing film laminate, the exposed side of the polarizing film was subjected to corona treatment. The resin composition (containing a solution of polyvinyl alcohol resin (manufactured by Japan VAM&POVAL Co., Ltd., trade name: JC-25H) with a degree of polymerization of 2500 and a degree of saponification of 99.8 mol% in pure water, and an aqueous solution of the water-soluble free radical scavenger represented by the above general formula (9) with a solid content of 25 wt%) was coated with a wire bar coater to achieve a thickness of 0.8 μm after drying. Then, it was dried at 60°C for 5 minutes to form a functional layer (reinforcing layer) on the polarizing film. Then, the first substrate was bonded by an aqueous adhesive. Otherwise, a polarizing film laminate with an adhesive layer was fabricated by the same operation as in Example 1.
[0091] <Comparative Example 1>
[0092] In the fabrication of the polarizing film, no compound represented by general formula (9) was added to the cleaning bath. Otherwise, a polarizing film laminate with an adhesive layer was fabricated by the same procedure as in Example 1.
[0093] <Comparative Example 2>
[0094] In the fabrication of the polarizing film, no compound represented by general formula (9) was added to the cleaning bath. Otherwise, a polarizing film laminate with an adhesive layer was fabricated by the same operation as in Example 2.
[0095] The polarizing film laminates with adhesive layers obtained in the above-described embodiments and comparative examples were used to evaluate the [monomer transmittance in a high-temperature environment]. The results are shown in Table 1.
[0096]
Claims
1. A polarizing film laminate, comprising a first substrate, a polarizing film, and a second substrate sequentially laminated. The moisture permeability of the first substrate and the second substrate is 300 g / (m²). 2 ·24h and below, At least one layer containing a water-soluble free radical scavenger exists between the first substrate and the second substrate. The water-soluble free radical scavenger is a compound having a nitryl radical or a nitryl group.
2. The polarizing film laminate according to claim 1, wherein, The total thickness of the layer existing between the first substrate and the second substrate is less than 50 μm.
3. The polarizing film laminate according to claim 1 or 2, wherein, At least one layer existing between the first substrate and the second substrate is selected from one or more of the polarizing film, adhesive layer, bonding agent layer, blocking layer, refractive index adjustment layer, reinforcing layer and liquid crystal coating.
4. The polarizing film laminate according to claim 1 or 2, wherein, The thickness of the polarizing film is less than 20 μm.
5. The polarizing film laminate according to claim 1 or 2, wherein, The polarizing film is an iodine-based polarizing film formed by adsorbing and orienting iodine.
Citation Information
Patent Citations
Production of high-purity (Meth)Acrylic acid ester
JP1999222462A
Method for diminishing n-oxyl compound
JP2002284737A
Method of producing polyfunctional vinyl compound
JP2003064022A
Polarizing element, polarizing plate, image display device, and method for manufacturing a polarizing element, all of which offer excellent durability and heat resistance.
JP2012516468A
Polarizing plate and image display device, and manufacturing method of those
JP2014102353A
